Effects of different fluences of low-level laser therapy in an experimental model of spinal cord injury in rats. Issue 2 (February 2017) - Veronez, Suellen; Assis, Lívia; Campo, Paula; Oliveira, Flávia; Castro, Gláucia; Renno, Ana; Medalha, Carla
Abstract The aim of this study was to evaluate the in vivo response of different fluences of low-level laser therapy (LLLT) on the area of the injury, inflammatory markers, and functional recovery using an experimental model of traumatic spinal cord injury (SCI). Thirty two rats were randomly divided into four experimental groups: control group (CG), laser-treated group 500 J/cm2 (L-500), laser-treated group 750 J/cm2 (L-750), and laser-treated group 1000 J/cm2 (L-1000). SCI was performed by an impactor equipment (between the ninth and tenth thoracic vertebrae), with a pressure of 150 kdyn. Afterwards, the injured region was irradiated daily for seven consecutive sessions, using an 808-nm laser, at the respective fluence of each experimental groups. Motor function and tactile sensitivity were performed on days 1 and 7 post-surgery. Animals were euthanized on the eighth day after injury, and the samples were retrieved for histological and immunohistochemistry analyses. Functional evaluation and tactile sensitivity were improved after LLLT, at the higher fluence. Additionally, LLLT, at 750 and 1000 J/cm2, reduces the lesion volume and modulates the inflammatory process with decrease of CD-68 protein expression. These results suggest that LLLT at higher doses was effective in promoting functional recovery and modulating inflammatory process in the spinal cord of rats after SCI.